Two distinct attachment sites for vimentin along the plasma membrane and the nuclear envelope in avian erythrocytes: a basis for a vectorial assembly of intermediate filaments (The Rockefeller University Press, 1987)
In vitro binding studies with isolated bovine lens vimentin and avian erythrocyte membranes reveal the existence of two functionally distinct sets of intermediate filament attachment sites. One population of such receptors is located along the nuclear envelope and comprises polypeptides recognizing the carboxy-terminal tail domain of vimentin. Vimentin associates with these nuclear surface receptors in a cooperative manner and forms extensive 10-nm filaments in a concentration-dependent fashion. Conversely, the plasma membrane contains binding sites that interact in a noncooperative, saturable fashion with vimentin, recognizing its amino-terminal head domain. The functional dichotomy of the vimentin-binding sites under in vitro conditions may reflect a vectorial assembly process whereby 10-nm filaments, although structurally apolar, acquire polar features brought about by the differential attachment to specific receptors arranged along the plasma membrane and the nuclear envelope.